2023
DOI: 10.1037/edu0000779
|View full text |Cite
|
Sign up to set email alerts
|

Individually endorsed and socially shared normative beliefs on acculturation: Resources and risk factors for academic and psychosocial adjustment in mid-adolescence.

Abstract: This article examines the extent to which normative beliefs on acculturation constitute (a) individual resources and risk factors for adolescents facing developmental tasks and (b) institutional norms that define developmental milieus in secondary schools. To what extent do egalitarianism, multiculturalism, assimilationism, and segregationism help or hinder academic and psychosocial adjustment in mid-adolescence? We examined how both individually endorsed beliefs and socially shared beliefs at the 10th-grade c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 100 publications
1
2
0
Order By: Relevance
“…Surprisingly, endorsement of a multiculturalism climate among majority peers was associated with decreased self-esteem among adolescents with immigrant background. However, this counterintuitive finding is consistent with critiques of the multiculturalism concept (Rios, 2022 ) and experimental findings by Wilton et al ( 2019 ), who reported increased negative self-stereotyping of minorities when ethnic categorizations were accentuated in a multiculturalism climate (Baumert et al, 2023 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Surprisingly, endorsement of a multiculturalism climate among majority peers was associated with decreased self-esteem among adolescents with immigrant background. However, this counterintuitive finding is consistent with critiques of the multiculturalism concept (Rios, 2022 ) and experimental findings by Wilton et al ( 2019 ), who reported increased negative self-stereotyping of minorities when ethnic categorizations were accentuated in a multiculturalism climate (Baumert et al, 2023 ).…”
Section: Discussionsupporting
confidence: 86%
“…Surprisingly, the normative diversity beliefs shared by majority group peers in schools—an important feature of adolescents’ proximal developmental environment (Suárez-Orozco et al, 2018 )—did not seem to be associated with cultural identity formation either (Hypothesis 1b). One explanation could be that cultural diversity is generally accepted among the younger generation (see Measures; Baumert et al, 2023 ), making schools—despite considerable variation in the diversity climate ( ICC = 0.22)—a developmental environment that may serve as a buffer against societal rejection. Alternative explanations are that diversity-friendly attitudes only reflect behavior to a limited extent and that discrimination and microaggressions also vary between schools, or that the diversity climate of a school is determined more by the acculturation beliefs of the faculty than by those of the student body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation